Gaming between places and identities: an investigation of table-top role-playing games as liminoid phenomena - Cloete, Stephen (My University, 2010)
Abstract This work explores the links between table-top role-playing games and the cultural anthropologist Victor Turner’s theory of liminoid phenomena, as described in his seminal essay Liminal to Liminoid, in Play, Flow, and Ritual: an Essay in Comparative Symbology. It explores the possibility of using Turner’s theory to better understand these games and their context within the broader cultural paradigm. It is argued that the complexity of these (and other) games, in particular the intricacy of interactions and behaviours that arise when players interpret potentially subversive written rule-sets, makes them hard to classify succinctly. There is however a great potential for linking table-top roleplaying to a wider body of academic theory regarding the function of ritual and pseudo-ritual behaviour in post-industrial societies through the auspices of Turner’s work.